Model Integrasi Sistem Produksi Multi Suplier Single Buyer Pada Sistem Just In Time - Wigati, Slamet Setio (Metris: Jurnal Sains dan Teknologi, 2016)
This research will discuss the integration of two suppliers single buyer in a Just In Time (JIT) environment. Supplier transform raw materials into semi-finished goods or components with a constant production rate. Buyer change of supplier components into a finished product with a constant production rate. Order quantity of the buyer are few innumber.If suppliers produce according to the buyerorder quantity, the expensive setup costs, then the supplier will produce the specified lot size to be sent multiple times to the buyer. The purpose of this research is to minimize the total joint inventory cost between suppliers and buyer, which includes setup cost and holding cost of the two supliers and order cost and holding cost of the buyer. The decision variables are theproduction lot and the number of deliveries in a single production lot both of supplier 1 and supplier 2. Numerical example and sensitivity analysis will be given in this research.